The Impact of Surroundings on the Characters in Thomas Hardy’s Novels - Rahman, Suzana; Muntiningsih, Ratna (Universitas Swadaya Gunung Jati, 2016)
The THE IMPACT OF SURROUNDINGS ON THE CHARACTERS INTHOMAS HARDY’S NOVELS” is to apply the writers’ knowledge on literature and toshow their interest in reading novels. The writers transfered not only their limitedknowledge in analysing novels as literary works but also building the awareness of theimportance of reading habit to their students of Unswagati because all of them take thesubject of Introduction to English Literature. Reading and analyzing novel is reallybeneficial for students that both can improve the students reading skill but also theirEnglish ability, moreover, they will have the ability in criticizing the novel fromdifferent views. In brief, it will also improve their critical thinking. Afterwards, bydescribing the characters and their attitudes toward each other and how thesurroundings influence them, we also learn about their culture. The theory that is usedin analysing those novels is from Harvey, Murphy, Klarer, and Lodge. The method thatis applied in analysing the characters and the surroundings is descriptive qualiative inwhich the writers take the data by reading the three novels, explain in details about thecharacters and the surroundings involved in the story and some other elementssupported the completeness of the story.